Inonotus obliquus polysaccharide are linear molecules that alter the abundance and composition of intestinal microbiota in Sprague Dawley rats - Liu, Songqing; Zhou, Wenjing; Deng, Xin; Jiang, Wei; Wang, Yanping; Zhan, Jiasui; Hu, Binhong (Frontiers in Nutrition, 2023)
The macromolecular polysaccharide Inonotus obliquus polysaccharide (IOP) is composed of various monosaccharides, and it has the ability to modulate the composition and diversity of intestinal flora. However, its impact on the intestinal flora in rats of different genders remains unclear. Therefore, this study aims to investigate the structural changes of IOP and its effects on the intestinal flora after administration in male and female rats. Herein, High-performance Gel Permeation Chromatography (HPGPC)analysis showed that the average molecular weight (Mw) of IOP was 4828 Da, and the total sugar content of the purified IOP is 96.2%, indicating that the polysaccharide is of high purity. Nuclear magnetic resonance (NMR) was used to determine the structure of the polysaccharide after purification, which revealed that IOP is a linear macromolecule with an α-D-type glucose backbone. Enzyme-linked immunosorbent assay (ELISA) and 16S rRNA were used to measure the levels of sex hormones (testosterone (T) and estradiol (E2))and intestinal microbiota, respectively. It was found that IOP increased the abundance of beneficial bacteria, such as Clostridia_UCG-014 and Prevotellaceae_NK3B31, and reduced that of harmful bacteria, such as Colidextribacter and Desulfobacterota in the intestine of both male and female rats. IOP dysregulated the secretion of sex hormones in male and female rats. Further analyses revealed that the increase in alpha diversity was higher in male than female rats. α diversity and β diversity revealed a significant difference in the composition of cecal microbiota between male and female rats in the control group, but IOP intake reduced this difference. Meanwhile, α analysis revealed a change in the composition of bacterial flora was more stable in male than female rats. In summary, this study enhances our comprehension of the IOP structure and elucidates the alterations in intestinal flora following IOP administration in rats of varying genders. Nonetheless, further investigation is warranted to explore the specific underlying reasons for these discrepancies.